The confabulating mind how the brain creates reality - Schnider, Armin (Oxford Oxford University Press, 2018)
Confabulation denotes the recitation of memories about events and experiences that never happened. Based on multiple case examples, The Confabulating Mind provides an in-depth review of the presentations, the causative diseases, and the mechanisms of this phenomenon and compares confabulation with normal false memories, as they occur in healthy adults and children. Memory-related confabulations are compared with false statements made by patients who confuse people, places, or their own health status, as this happens in disorders like déjà vu, paramnesic misidentification, and anosognosia.
The reality of Mrs B -- The history of confabulation -- Types of confabulation -- Aetiologies and anatomy of confabulation -- Disorders associated with confabulation -- Normal false memory -- Mechanisms of confabulation -- Orbitofrontal reality filtering -- Perspectives.
Previous edition: 2008.
Includes bibliographical references and indexes.
Keywords: False memory syndrome; Repression, Psychology; Brain -- Physiology; Denial (Psychology); Perceptual Defense